2021
DOI: 10.3390/jcm10051040
|View full text |Cite
|
Sign up to set email alerts
|

Cutaneous Manifestations in Biological-Treated Inflammatory Bowel Disease Patients: A Narrative Review

Abstract: The biologic era has greatly improved the treatment of Crohn’s disease and ulcerative colitis. Biologics can however induce a wide variety of skin eruptions, especially those targeting the TNF-α and Th17 pathway. These include infusion reactions, eczema, psoriasis, lupus, alopecia areata, vitiligo, lichenoid reactions, granulomatous disorders, vasculitis, skin cancer, and cutaneous infections. It is important to recognize these conditions as treatment-induced adverse reactions and adapt the treatment strategy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 87 publications
(38 reference statements)
0
12
0
Order By: Relevance
“…Paradoxically, side effects of these immunosuppressive regimens can include inflammatory skin eruptions. Literature estimates incidences of 4%–7% for psoriasiform and 3%–9% for eczematous eruptions in adults with IBD, 2 while one prospective study of children with IBD on infliximab found a combined incidence as high as 48% (40/84) 3 . The prospective nature of the study and inclusion of only children on infliximab likely contributed to the higher incidence of psoriasiform and eczematous eruptions in this study.…”
Section: Introductionmentioning
confidence: 70%
“…Paradoxically, side effects of these immunosuppressive regimens can include inflammatory skin eruptions. Literature estimates incidences of 4%–7% for psoriasiform and 3%–9% for eczematous eruptions in adults with IBD, 2 while one prospective study of children with IBD on infliximab found a combined incidence as high as 48% (40/84) 3 . The prospective nature of the study and inclusion of only children on infliximab likely contributed to the higher incidence of psoriasiform and eczematous eruptions in this study.…”
Section: Introductionmentioning
confidence: 70%
“…Additionally, IBD patients had several intrinsic risk factors that play a key role in the development of infections, including malnutrition, surgery, and “leaky gut syndrome”, with consequent increased pathogen exposure and bacterial translocation, especially when co-treated with steroids that could contribute to the observed increase in infection rates [ 54 , 55 , 56 ]. Anti-TNFα agents, particularly ADA, followed by UST and VED, play a role in the onset of dermatological pathologies, including urticaria, erythema, and dermatitis [ 57 ]; moreover, our data showed a higher incidence of malignancies with VED when adjusted on 10 years of treatment. Chronic inflammation is more frequently related to colorectal cancer development and extraintestinal neoplasms in IBD patients than in the general population [ 58 , 59 ].…”
Section: Discussionmentioning
confidence: 87%
“…30 There is little evidence of importance for integrin α4β7 in cutaneous inflammation, due to lack of MAdCAM-1 receptor expression in skin and low rates of cutaneous adverse events following treatment with α4β7 (vedolizumab). 31 Early on, CD103 and αEβ7 had been used as a specific marker for intestinal intraepithelial T cells but was soon found to be expressed by other cell types, including dendritic cells, mast cells, and ILCs. 32 Although up-regulation of αEβ7 was shown to promote retention of T RM in epithelial tissues, 33 the presence of CD103 + T cells in organs with low e-cadherin expression argues for more complex consequences on T-cell homing that are yet to be defined.…”
Section: T Rm Composition and Phenotype In Adult Skinmentioning
confidence: 99%